Two-fold interpenetrated Mn-based metal–organic frameworks (MOFs) as battery-type electrode materials for charge storage. Issue 2 (13th December 2019) - Wang, Kuaibing; Lv, Bo; Wang, Zikai; Wu, Hua; Xu, Jiangyan; Zhang, Qichun
Abstract : Two novel interpenetrated 2-fold Mn-MOFs were successfully prepared and applied for the first time in a charge-storage field. As a result, the bulk electrodes behave as alkaline batteries and deliver high capacities of 1004 and 619 C g −1 at 1 A g −1 . Abstract : Two novel interpenetrated 2-fold Mn-based metal–organic frameworks (MOFs) (SC-7 and SC-8), assembled from the rigid ligand H3 TATB (4, 4′, 4′′- s -triazine-2, 4, 6-triyl-tribenzoic acid) and Mn ions with the assistance of the flexible N-donor linker BIB (bis((1 H -imidazol-1-yl)methyl)benzene) or TIPA (tris(4-imidazolylphenyl)amine), have been successfully prepared. The as-obtained MOFs show two distinct topological structures with the symbols 4 4 ·6 2 and (5 2 ·6)(5 3 ·6·7 3 ·8 2 ·9) due to discrepancies between the flexibilities of the bi-imidazole and tri-imidazole linkers. The electrodes based on the as-prepared bulk Mn-MOFs behave as alkaline batteries in electrochemical cells and deliver high capacities (279 and 172 mA h g −1 at 1 A g −1 for SC-7 and SC-8, respectively). Theoretical mechanism analyses indicate that the surface-controlled ( k 1 v ) process can be transformed into a diffusion-dominated ( k 2 v 1/2 ) process when the charging time exceeds 30 seconds in the MOF-based systems. Our research provides a new strategy to construct an increasing number of stable redox sites in MOFs for application to battery-capacitor hybrid devices.